2015
DOI: 10.1021/acs.joc.5b01686
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic and Immunological Studies of Mycobacterial Lipoarabinomannan Oligosaccharides and Their Protein Conjugates

Abstract: Lipoarabinomannan (LAM) is one of the major constituents of the Mycobacterium tuberculosis cell wall and an attractive molecular scaffold for antituberculosis drug and vaccine development. In this paper, a convergent strategy was developed for the synthesis of LAM oligosaccharides with an α-1,2-linked dimannopyranose cap at the nonreducing end. The strategy was highlighted by efficient coupling of separately prepared nonreducing end and reducing end oligosaccharides. Glycosylations were mainly achieved with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 56 publications
0
46
0
Order By: Relevance
“…1927,44 A recent investigation by Guo's group verified the synthetic and immunological potential of protein conjugated ManLAM fragments. 28 However, far too little attention has been paid to synthesizing the large oligomers in ManLAM. The main aim of the current research has therefore been to synthesize naturally occurring large oligosaccharide portions of ManLAM such as arabinomannan 1 (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…1927,44 A recent investigation by Guo's group verified the synthetic and immunological potential of protein conjugated ManLAM fragments. 28 However, far too little attention has been paid to synthesizing the large oligomers in ManLAM. The main aim of the current research has therefore been to synthesize naturally occurring large oligosaccharide portions of ManLAM such as arabinomannan 1 (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The cell‐wall oligosaccharides produced by bacteria are another example of branched and complex oligosaccharide structures. Such oligomers are composed of repeating units of furanose and, because the structures are unique to each bacterial strain, they have been used as epitopes for vaccines against bacterial pathogens . The critical question is: which fragments of an oligosaccharide and how many repeating units are sufficient to elicit robust immune response?…”
Section: Methodsmentioning
confidence: 99%
“…A number of bacterial glycans [1,2] are specific markers for the detection and the serological identification of microorganisms [3][4][5] and are widely used as antigenic components of vaccines [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. The use of gold nanoparticles (GNPs) [24][25][26] as carriers for glyco-epitopes is becoming an important alternative [15, to the traditional conjugation with proteins, synthetic polymers and other carriers [15,17,38,[49][50][51][52][53][54][55].…”
Section: Introductionmentioning
confidence: 99%
“…Lipoarabinomannan (LAM) and the related arabinogalactan (AG) are two major structural components of the M. tuberculosis cell wall. Previous studies revealed that LAM and especially its terminal oligosaccharide fragments, conjugated with proteins [7,10,19] or monophosphoryl lipid A [23], are attractive targets for the development of carbohydrate-based anti-TB vaccines [7,10,19,23,65,66].…”
Section: Introductionmentioning
confidence: 99%